Analysis of Data Encryption Algorithms for Telecommunication Network-Computer Network Communication Security. (13th November 2021) - He, Yifeng; Ye, Nan; Zhang, Rui
Abstract : Nowadays, the development of information technology can be described as extremely rapid, especially with the widespread use of the Internet; the security of communications in the network has become an important issue we are facing. The purpose of this article is to solve the problems in today's network security data encryption algorithms. Starting from the computer network communication security data encryption algorithm, we discuss the effects of several different encryption methods on improving network security. The research results show that it is known that the application of link encryption algorithm in network communication security encryption algorithm can increase the security index by 25%, the node encryption algorithm can increase the security index by 35%, and the end-to-end encryption algorithm can make the cyber activity safety index to increase by 40%. Among them, RSA algorithm and DES algorithm are two very representative algorithms; they represent different encryption systems. From the perspective of network data link, there are three methods of encryption algorithm, namely, link encryption algorithm, node encryption algorithm, and end-to-end encryption algorithm.